STING induces early IFN-β in the liver and constrains myeloid cell-mediated dissemination of murine cytomegalovirus - Pia-Katharina Tegtmeyer (Nature Portfolio, 2019)
Innate immune signaling pathways sense different microbial features and can elicit distinct yet overlapping immune responses. Here the authors dissect the contribution of these pathways to the response to MCMV infection and find that STING signaling is dispensable for host survival but crucial to restrict viral replication and dissemination via myeloid cells.